If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 22 = 4f + -6 Reorder the terms: 22 = -6 + 4f Solving 22 = -6 + 4f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-4f' to each side of the equation. 22 + -4f = -6 + 4f + -4f Combine like terms: 4f + -4f = 0 22 + -4f = -6 + 0 22 + -4f = -6 Add '-22' to each side of the equation. 22 + -22 + -4f = -6 + -22 Combine like terms: 22 + -22 = 0 0 + -4f = -6 + -22 -4f = -6 + -22 Combine like terms: -6 + -22 = -28 -4f = -28 Divide each side by '-4'. f = 7 Simplifying f = 7
| -9-2x=-5 | | -3r^2-9r=0 | | 9(u-3)=6u-48 | | v^2+10v=5 | | 4-3w=4w+w-7 | | 2x+2a=4b | | -5(7+m)=-125 | | 7-8v=3v-8 | | 4=6+x/3 | | 4+7(x-2x)=60 | | 2n-5n=-3 | | -4.9x+6.88x-1.25=0 | | -35-2r=-3r+4(2r-7) | | 21+8p=-2(4-p)-7 | | p-2/6=p-4 | | a+b-c=d | | 5h+2-(h)=22 | | 7=7-10x | | -4.9x+7.25x-1.25=0 | | 9+4y=2(3-1) | | 2.3+3n=0.8n+12 | | 2(x-4)+3x=4(x-5) | | 5.5-10=11 | | 106=2(-6b+5) | | =500(1.05)(9) | | 13=4p+5+4p | | 2x-27y+11xy=22 | | [x-5]=[x+2] | | 5=1-4a-8 | | 3x+y-8x+2y= | | 3(1-4x)+2(7x)=25 | | -8(4+9r)=7*(-2-11r) |